A prospective survey study on the education and awareness about walking exercise amongst inpatients with symptomatic peripheral arterial disease in Germany - Li, Yi; Rother, Ulrich; Rosenberg, Yvonne; Hinterseher, Irene; Uhl, Christian; Mylonas, Spyridon; Grambow, Eberhard; Gombert, Alexander; Busch, Albert; Bresler, Ayko; Öz, Tugce; Görtz, Hartmut; et al. (Vasa-Journal of Vascular Diseases, 2023)
Summary: Background: To determine the adherence to supervised exercise training and underlying reasons for non-adherence amongst patients with inpatient treatment of symptomatic lower extremity peripheral arterial disease (PAD). Patients: This was a prospective questionnaire-based survey study of all consecutively treated inpatients with treatment for either intermittent claudication or chronic limb-threatening ischaemia (CLTI) surveyed at sixteen participating centres in Germany. Results: A total of 235 patients (median age 70 years) were included, thereof 29.4% females and 34.6% with CLTI. The median time from first PAD diagnosis was 4 years (IQR: 1-8). Only 11.4% have previously participated in any walking exercise programme before the index treatment, thereby 10.0% in the IC subgroup and 12.0% with CLTI. Amongst all patients, 35.6% responded they were appropriately informed about the necessity and benefits of walking exercise programmes by their hospital physicians (25.8% by general practitioners), and 65.3% agreed that adherence to supervised exercise may improve their pain-free walking distance. A total of 24.5% responded they had access to necessary information concerning local walking exercise programmes. Amongst 127 free text comments on the reasons for non-adherence to supervised exercise training, 64% of the comments contained lack of information or consent on such measures. Conclusions: Less than 12% of the patients enrolled in the current study have ever participated in a walking exercise programme during their life course. Although all practice guidelines contain corresponding class I recommendations, especially for patients suffering from IC, most patients responded that they were not appropriately informed about the necessity of exercise training along with the fact that 65% agreed that exercise may increase the pain-free walking distance. Taken all together, these results emphasise that we miss an important opportunity in the patient-physician communication. Efforts should be made to improve acceptance and application of structured walking-exercise for patients with PAD.
CRIS-Team Scopus Importer:2023-02-17
Keywords: best medical treatment; health behaviour; health services research; intermittent claudication; peripheral arterial disease; Walking exercise

Automatic Muscle Segmentation for the Diagnosis of Peripheral Artery Disease Using Multispectral Optoacoustic Tomography - Schillinger, Moritz; Schlereth, Maja; Boraud, Gaspard; Zahnd, Guillaume; Dehner, Christoph; Li, Yi; Kempf, Julius; Caranovic, Milenko; Haney, Briain; Rother, Ulrich; Breininger, Katharina (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
Multispectral optoacoustic tomography (MSOT) is a medical imaging modality capable of visualizing chromophore concentrations, such as oxygenated (HbO2) and deoxygenated hemoglobin (Hb), making it particularly useful for diagnosing blood-perfusion-related diseases like peripheral artery disease (PAD). Previous MSOT-based diagnostic studies involved experts manually selecting a region of interest (ROI) with a predefined shape in the target muscle to analyze blood oxygenation. This study aims to automate this process using a deep-learning-based approach. We present a pipeline that uses co-registered ultrasound images to automatically place an ROI necessary for PAD diagnosis in the MSOT image by training a deep-learning-based segmentation model to locate the target muscle. The resulting segmentation mask is overlaid onto the corresponding optoacoustic image to extract mean HbO2 and Hb intensities within the ROIs. We evaluated our pipeline on two separate PAD-related MSOT-datasets. When comparing blood oxygenation in the automatically generated ROIs on the MSOT images to identify PAD patients, we achieved areas under the ROC curve (AUCs) of 0.87 (vs. 0.85 for manually drawn ROIs) and 0.76 (vs. 0.77 for manually drawn ROIs) on the respective datasets. Our results indicate that optoacoustic ROI placement using deep-learning-based ultrasound segmentation is feasible and performs comparably to manually drawn ROIs by clinical experts. This approach could reduce the annotation effort in future MSOT studies and provide an ROI with greater physiological relevance compared to the arbitrary shapes used in related MSOT research. Future work could extend this approach to other body sites and diseases.
CRIS-Team Scopus Importer:2025-05-16

Detection of wound healing disorders after major amputations by measurements of the microcirculation: A prospective single-center study - Zetzmann, Katharina; Papatheodorou, Nikolaos; Rühl, Eva; Yagshyyev, Shatlyk; Haney, Briain; Moosmann, Oxana; Li, Yi; Meyer, Alexander; Knieling, Ferdinand; Behrendt, Christian Alexander; Lang, Werner; Rother, Ulrich (SAGE Open Medicine, 2024)
Introduction: Although major amputations can often be avoided due to evolving methods of endovascular and surgical revascularizations techniques, in patients with chronic limb-threatening ischemia, it is still necessary in some cases. Aim of this study was the detection of wound healing disorders through intraoperative microcirculation measurements in major limb amputations. Materials and methods: In this single-center clinical study, patients with an indication for major amputation were enrolled prospectively. Cause of amputation, patients’ comorbidities including cardiovascular risk profile were assessed. Macrocirculation, as well as microcirculation were assessed. Microcirculation measurements were performed by fluorescence angiography with the administration of indocyanine green. A preoperative measurement was obtained at the amputation level, followed by three additional measurements of the amputation stump postoperatively. Wound healing was monitored and correlated with the microcirculatory findings, based on the perfusion parameters ingress and ingress rate, calculated in the indocyanine green fluorescence video sequences of the amputation stumps. Results: Forty-five patients were enrolled, including 19 (42%) below-the-knee amputations and 26 (58%) above-the-knee amputations. When considering the need for revision, a change in the microperfusion parameters was observed postoperatively. The mean value for ingress was significantly lower directly postoperatively in stumps requiring revisions (5 ± 0 A.U. versus 40.5 ± 42.5 A.U., p < 0.001). The mean value of ingress rate behaved similarly (0.15 ± 0.07 A.U./s versus 2.8 ± 5.0 A.U./s, p = 0.005). The evaluation of indocyanine green measurements when wound healing disorders occurred also showed nonsignificant differences in the mean values. Conclusion: Fluorescence angiography after major lower limb amputations appears to be an option of depicting microperfusion. Especially, the early postoperative detection of reduced perfusion can indicate a subsequent need for revision. Therefore, this method could possibly serve as a tool for intraoperative quality control after major limb amputation.
CRIS-Team Scopus Importer:2024-08-02
Keywords: fluorescence angiography; indocyanine green; Major limb amputation; microperfusion; wound healing

Effect of Flat-Knitted Medical Compression Stockings on Venous Malformations - Li, Yi; Muekke, Antje; Rother, Ulrich; Janka, Rolf Matthias; Uder, Michael; Lang, Werner; Heiß, Rafael (Journal of Clinical Medicine, 2023)
Venous malformations are one of the most common vascular anomalies. Our study aimed to investigate the effect of medical compression stockings of class I and II on the volume of venous malformations. Patients with venous malformations on upper or lower extremities were enrolled. They wore flat-knitted medical compression stockings of class I and II in a randomized order for four weeks each. Magnetic resonance imaging (MRI) and perometry were performed with and without wearing compression stockings. The 12-Item Short Form Survey (SF-12) questionnaire was performed before and after wearing compression stockings for four weeks each. A total of 18 patients completed the evaluations. Both compression classes showed a significant reduction of the volume of the venous malformations in the lesion itself based on MRI in comparison with baseline (both p < 0.001). Measurements taken with perometry did not reveal a significant difference in comparison to baseline (p = 0.09 and p = 0.22). The results of the SF-12 questionnaire demonstrated no significant differences before and after wearing the compression stockings of class I or class II for four weeks or between the two classes of compression therapy. Our results indicate that wearing medical compression stockings of both class I and class II significantly reduces the volume of venous malformation, without compromising the quality of life, while the effect of class II compression stockings on volume reduction was significantly better than that of class I.
CRIS-Team Scopus Importer:2023-04-28
Keywords: compression stockings; magnetic resonance imaging; perometry; quality of life; T2-weighted imaging; venous malformation

Fibroblast Subpopulations in Systemic Sclerosis: Functional Implications of Individual Subpopulations and Correlations with Clinical Features - Zhu, Honglin; Luo, Hui; Skaug, Brian; Tabib, Tracy; Li, Yi; Tao, Yongguang; Matei, Alexandru-Emil; Lyons, Marka A.; Schett, Georg; Lafyatis, Robert; Assassi, Shervin; Distler, Jörg (Journal of Investigative Dermatology, 2024)
Fibroblasts constitute a heterogeneous population of cells. In this study, we integrated single-cell RNA-sequencing and bulk RNA-sequencing data as well as clinical information to study the role of individual fibroblast populations in systemic sclerosis (SSc). SSc skin demonstrated an increased abundance of COMP+, COL11A1+, MYOC+, CCL19+, SFRP4/SFRP2+, and PRSS23/SFRP2+ fibroblasts signatures and decreased proportions of CXCL12+ and PI16+ fibroblast signatures in the Prospective Registry of Early Systemic Sclerosis and Genetics versus Environment in Scleroderma Outcome Study cohorts. Numerical differences were confirmed by multicolor immunofluorescence for selected fibroblast populations. COMP+, COL11A1+, SFRP4/SFRP2+, PRSS23/SFRP2+, and PI16+ fibroblasts were similarly altered between normal wound healing and patients with SSc. The proportions of profibrotic COMP+, COL11A1+, SFRP4/SFRP2+, and PRSS23/SFRP2+ and proinflammatory CCL19+ fibroblast signatures were positively correlated with clinical and histopathological parameters of skin fibrosis, whereas signatures of CXCL12+ and PI16+ fibroblasts were inversely correlated. Incorporating the proportions of COMP+, COL11A1+, SFRP4/SFRP2+, and PRSS23/SFRP2+ fibroblast signatures into machine learning models improved the classification of patients with SSc into those with progressive versus stable skin fibrosis. In summary, the profound imbalance of fibroblast subpopulations in SSc may drive the progression of skin fibrosis. Specific targeting of disease-relevant fibroblast populations may offer opportunities for the treatment of SSc and other fibrotic diseases.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Dermal fibrosis; Disease outcomes; Fibroblasts; SSc; Subpopulations

Hybrid ultrasound and single wavelength optoacoustic imaging reveals muscle degeneration in peripheral artery disease - Träger, Anna P.; Günther, Josefine; Raming, Roman; Paulus, Lars-Philip; Lang, Werner; Meyer, Alexander; Kempf, Julius; Caranovic, Milenko; Li, Yi; Wagner, Alexandra; Tan, Lina; Danko, Vera; et al. (Photoacoustics, 2024)
Peripheral arterial disease (PAD) leads to chronic vascular occlusion and results in end organ damage in critically perfused limbs. There are currently no clinical methods available to determine the muscular damage induced by chronic mal-perfusion. This monocentric prospective cross-sectional study investigated n = 193 adults, healthy to severe PAD, in order to quantify the degree of calf muscle degeneration caused by PAD using a non-invasive hybrid ultrasound and single wavelength optoacoustic imaging (US/SWL-OAI) approach. While US provides morphologic information, SWL-OAI visualizes the absorption of pulsed laser light and the resulting sound waves from molecules undergoing thermoelastic expansion. US/SWL-OAI was compared to multispectral data, clinical disease severity, angiographic findings, phantom experiments, and histological examinations from calf muscle biopsies. We were able to show that synergistic use of US/SWL-OAI is most likely to map clinical degeneration of the muscle and progressive PAD.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Muscle degeneration; Muscle imaging; Optoacoustics; Peripheral artery disease; Photoacoustics

Independent Factors Influencing Changes in Baroreceptor Sensitivity after Carotid Endarterectomy - Yagshyyev, Shatlyk; Haney, Briain; Li, Yi; Papatheodorou, Nikolaos; Zetzmann, Katharina; Meyer, Alexander; Meyer, Sebastian; Lang, Werner; Rother, Ulrich (Annals of Vascular Surgery, 2024)
Background: Carotid endarterectomy (CEA) is a well-established standard therapy for patients with symptomatic or asymptomatic high-grade carotid stenosis. The aim of carotid endarterectomy is to decrease the risk of stroke and avoid relevant functional loss. However, carotid endarterectomy is known to be associated with hemodynamic dysregulation. In this study we compared eversion CEA (E-CEA) and conventional CEA (C-CEA) regarding postoperative blood pressure values as well as preoperative and postoperative baroreceptor sensitivity in the first 7 days after surgery. The aim was to find possible factors influencing changes in baroreceptor sensitivity. Methods: Patients (111 patients were enrolled, of which 50 patients received C-CEA and 61 patients E-CEA) were prospectively enrolled in this study. For the measurement of baroreceptor sensitivity, a noninvasive Finometer measuring device from Finapres Medical System B.V. (Amsterdam, The Netherlands) was used. Measurements were performed 1 day before surgery (PRE), directly after surgery (F1), on day 1 (F2), day 2 (F3), and on day 7 (F4) postoperatively. Results: Postoperative blood pressure values were significantly higher in the E-CEA group on the day of surgery (F1) (P < 0.001) and on day 1 (F2) (P < 0.001). From day 2 (F3, F4) postoperatively, no significant difference was found between the 2 groups. The invasive blood pressure measurement in the postoperative recovery room showed significantly higher systolic blood pressure values in the E-CEA group (P = 0.001). The need of acute antihypertensive therapy was significantly higher in the recovery room in the E-CEA group (P = 0.020). With regard to changes in baroreceptor sensitivity, significantly lower baroreceptor sensitivity (BRS) values were recorded in the E-CEA group at 1 day (F2) postoperatively (P = 0.005). The regression analysis showed that the applied surgical technique and the patient's age were significant factors influencing changes in baroreceptor sensitivity. Conclusions: In this study we could confirm higher blood pressure levels after E-CEA in the first 2 days after surgery. Additionally, we identified 22 factors possibly influencing baroreceptor sensitivity: surgical technique and age. Based on the data obtained in this study, hemodynamic dysregulation after CEA (E-CEA, C-CEA) is temporary and short-term. Already after the second postoperative day, there was no significant difference between the E-CEA and E-CEA groups, this effect remained stable after 7 days.
CRIS-Team Scopus Importer:2024-08-09

Intermittent negative pressure therapy in patients with no-option chronic limb-threatening ischemia - Yagshyyev, Shatlyk; Hausmann, Philipp; Li, Yi; Kempf, Julius; Zetzmann, Katharina; Dessi, Katia; Moosmann, Oxana; Almási-Sperling, Veronika; Meyer, Alexander; Gerken, Andreas L.H.; Lang, Werner; Rother, Ulrich (Vasa-Journal of Vascular Diseases, 2023)
Background: Aim of this study was to assess the influence of intermitted negative pressure (INP) therapy on the foot microcirculation in patients with no-option CLTI. Patients and methods: CLTI patients defined as no option for revascularization on the basis of an interdisciplinary vascular board decision (interventional radiology, vascular surgery) were included in this study. INP therapy was performed at home. Therapy regime was: 1 hour twice daily. Follow-up was after 6 weeks and 3 months. Microcirculation measurement was performed by laser Doppler flowmetry and white light spectrometry (oxygen to see, O2CTM). Following parameters were evaluated: oxygen saturation (sO2 in%), relative hemoglobin (rHb) and flow (in arbitrary units A.U.). Additionally the clinical outcome of the patients was assessed. Results: From September 2020 to June 2022, 228 patients were screened. In total 19 patients (13 men, 6 women, mean age was 73.95 years) were included. 6 weeks after INP therapy the microcirculation showed a significant improvement for the parameter sO2 (%) (p=0.004). After 3 months a non-significant decrease compared to 6 weeks follow-up was seen for the parameter sO2; however, the perfusion was still improved compared to baseline measurement. With regard to the microperfusion values flow (AU) and hemoglobin (AU), the changes were not significant. Clinically, the patients reported a significant reduction of rest pain after therapy (p=0.005). Conclusions: INP therapy in no-option CLTI patients showed a significant improvement of the skin perfusion after 6 weeks. Therefore, INP therapy might have therapeutic potential in these critical ill patients.
CRIS-Team Scopus Importer:2023-11-17
Keywords: chronic limb-threating ischemia; FlowOx; intermittent negative pressure; microperfusion; no-option patients; oxygen to see (O2C)

Non-invasive optoacoustic imaging of glycogen-storage and muscle degeneration in late-onset Pompe disease. - Tan, Lina; Zschüntzsch, Jana; Meyer, Stefanie; Stobbe, Alica; Bruex, Hannah; Regensburger, Adrian; Claßen, Merle; Alves, Frauke; Jüngert, Jörg; Rother, Ulrich; Li, Yi; Danko, Vera; et al. (Nature Communications, 2024)
Pompe disease (PD) is a rare autosomal recessive glycogen storage disorder that causes proximal muscle weakness and loss of respiratory function. While enzyme replacement therapy (ERT) is the only effective treatment, biomarkers for disease monitoring are scarce. Following ex vivo biomarker validation in phantom studies, we apply multispectral optoacoustic tomography (MSOT), a laser- and ultrasound-based non-invasive imaging approach, in a clinical trial (NCT05083806) to image the biceps muscles of 10 late-onset PD (LOPD) patients and 10 matched healthy controls. MSOT is compared with muscle magnetic resonance imaging (MRI), ultrasound, spirometry, muscle testing and quality of life scores. Next, results are validated in an independent LOPD patient cohort from a second clinical site. Our study demonstrates that MSOT enables imaging of subcellular disease pathology with increases in glycogen/water, collagen and lipid signals, providing higher sensitivity in detecting muscle degeneration than current methods. This translational approach suggests implementation in the complex care of these rare disease patients.
EVALuna2:571098

Peri-Prosthetic Fracture as a Rare Cause of Critical Limb Ischaemia - Li, Yi; Schmid, Axel (European Journal of Vascular and Endovascular Surgery, 2023)
CRIS-Team Scopus Importer:2023-04-28

Shortcut learning leads to sex bias in deep learning models for photoacoustic tomography - Knopp, Marcel; Bender, Christoph J.; Holzwarth, Niklas; Li, Yi; Kempf, Julius; Caranovic, Milenko; Knieling, Ferdinand; Lang, Werner; Rother, Ulrich; Seitel, Alexander; Maier-Hein, Lena; Dreher, Kris K. (International Journal of Computer Assisted Radiology and Surgery, 2025)
Purpose: Shortcut learning has been identified as a source of algorithmic unfairness in medical imaging artificial intelligence (AI), but its impact on photoacoustic tomography (PAT), particularly concerning sex bias, remains underexplored. This study investigates this issue using peripheral artery disease (PAD) diagnosis as a specific clinical application. Methods: To examine the potential for sex bias due to shortcut learning in convolutional neural network (CNNs) and assess how such biases might affect diagnostic predictions, we created training and test datasets with varying PAD prevalence between sexes. Using these datasets, we explored (1) whether CNNs can classify the sex from imaging data, (2) how sex-specific prevalence shifts impact PAD diagnosis performance and underdiagnosis disparity between sexes, and (3) how similarly CNNs encode sex and PAD features. Results: Our study with 147 individuals demonstrates that CNNs can classify the sex from calf muscle PAT images, achieving an AUROC of 0.75. For PAD diagnosis, models trained on data with imbalanced sex-specific disease prevalence experienced significant performance drops (up to 0.21 AUROC) when applied to balanced test sets. Additionally, greater imbalances in sex-specific prevalence within the training data exacerbated underdiagnosis disparities between sexes. Finally, we identify evidence of shortcut learning by demonstrating the effective reuse of learned feature representations between PAD diagnosis and sex classification tasks. Conclusion: CNN-based models trained on PAT data may engage in shortcut learning by leveraging sex-related features, leading to biased and unreliable diagnostic predictions. Addressing demographic-specific prevalence imbalances and preventing shortcut learning is critical for developing models in the medical field that are both accurate and equitable across diverse patient populations.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Peripheral artery disease (PAD); Photoacoustic tomography (PAT); Sex Bias in AI; Shortcut learning

Teachability of multispectral optoacoustic tomography - Li, Yi; Gröhl, Janek; Haney, Briain; Caranovic, Milenko; Lorenz-Meyer, Eva; Papatheodorou, Nikolaos; Kempf, Julius; Regensburger, Adrian; Nedoschill, Emmanuel; Bühler, Adrian; Siebenlist, Gregor; Lang, Werner; et al. (Journal of Biophotonics, 2024)
To date, the appropriate training required for the reproducible operation of multispectral optoacoustic tomography (MSOT) is poorly discussed. Therefore, the aim of this study was to assess the teachability of MSOT imaging. Five operators (two experienced and three inexperienced) performed repositioning imaging experiments. The inexperienced received the following introductions: personal supervision, video meeting, or printed introduction. The task was to image the exact same position on the calf muscle for seven times on five volunteers in two rounds of investigations. In the first session, operators used ultrasound guidance during measurements while using only photoacoustic data in the second session. The performance comparison was carried out with full-reference image quality measures to quantitatively assess the difference between repeated scans. The study demonstrates that given a personal supervision and hybrid ultrasound real-time imaging in MSOT measurements, inexperienced operators are able to achieve the same level as experienced operators in terms of repositioning accuracy.
CRIS-Team Scopus Importer:2024-05-17
Keywords: MSOT; multispectral optoacoustic imaging; teachability; ultrasound